2020
DOI: 10.1002/mp.14467
|View full text |Cite
|
Sign up to set email alerts
|

Automatic contouring system for cervical cancer using convolutional neural networks

Abstract: To develop a tool for the automatic contouring of clinical treatment volumes (CTVs) and normal tissues for radiotherapy treatment planning in cervical cancer patients. Methods: An auto-contouring tool based on convolutional neural networks (CNN) was developed to delineate three cervical CTVs and 11 normal structures (seven OARs, four bony structures) in cervical cancer treatment for use with the Radiation Planning Assistant, a web-based automatic plan generation system. A total of 2254 retrospective clinical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
77
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(88 citation statements)
references
References 45 publications
7
77
4
Order By: Relevance
“…However, despite promising segmentation results their framework was only evaluated on patient scans from a single institution. In contrast, Rhee et al [94] used a VNet model to generate CT treatment plans and reported that their algorithm achieved on average 80%, 97% and 90% clinical acceptance rate for primary CTVs, OARs and bony structures respectively. Their framework was validated on 30 cervical cancer patients scanned across three hospitals.…”
Section: Cervical Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite promising segmentation results their framework was only evaluated on patient scans from a single institution. In contrast, Rhee et al [94] used a VNet model to generate CT treatment plans and reported that their algorithm achieved on average 80%, 97% and 90% clinical acceptance rate for primary CTVs, OARs and bony structures respectively. Their framework was validated on 30 cervical cancer patients scanned across three hospitals.…”
Section: Cervical Cancermentioning
confidence: 99%
“…MRI is more accurate in the diagnosis, staging and treatment planning of rectal cancer compared with CT, and also provides quantitative tumor assessment, which can inform treatment response assessment and disease outcomes [170]. Although in recent years numerous studies were published for automatic contouring of pelvic tumors [94,[171][172][173][174], only a few were reported to address rectal cancer [27,146,175]. Based on our article search, 9 studies incorporated DL for rectal cancer segmentation applications (CT: 2, MRI: 6, MRI/CT: 1) (Table 1).…”
Section: Rectal Cancermentioning
confidence: 99%
“…In this study, we propose a fully automated coarse-tofine segmentation approach using convolutional neural networks (CNNs) to accurately and efficiently segment OARs in female pelvic MR images. While CT-based pelvic OAR segmentation has been actively studied, [4][5][6][7][8] there are few studies of automatic segmentation of pelvic MR images, with most existing studies focused on male pelvic OARs for prostate cancer diagnosis and treatment. 9 Segmenting OARs in MR images may be considered easier than CT given superior soft tissue image contrast.…”
Section: Introductionmentioning
confidence: 99%
“…Deep learning (DL) has been applied with success in proofs of concept across biomedical imaging modalities and medical specialties [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . DL models can classify images by disease or structure and can segment, track, and measure structures within images.…”
Section: Introductionmentioning
confidence: 99%